Krigens lyd, krigens musik. Nye dimensioner til krigens kulturanalyse - Koldau, Linda Maria (Passage - Tidsskrift for litteratur og kritik, 2011)
Linda Maria Koldau: “The Sound of War, the Music of War” The article shows how the aural dimension of warfare shapes the experience and memory of war. In Danish reflections on the day of the German invasion (exemplified by passages from literature and film), this is primarily represented by the drone of the German airforce, which has become an aural symbol for the occupation and thus for war coming to Denmark.